Contextual Interference Effects on Learning Volleyball Skills - Koufou, Νεραντζούλα; Michalopoulos, Μαρία; Kioumourtzoglou, Ευθύµης (Inquiries in Physical Education and Sport, 2003)
The aim of the current study was to examine the contextual interference effects on learning three volleyball skills: overhand pass, forearm pass and underhand serve during physical education classes. The sample was 117 high school students (63 boys, 53 girls) aged between 12-14 years, (M=12.99, SD=0.59 years). The subjects were randomly assigned to three equally sized groups (n=39), two experimental –blocked and serial practice groups- and one control group. The experimental groups practiced each volleyball skill for 135 trials, 45 trials at every session, for 9 consecutive physical education sessions. Pretests took place at the beginning of the practice phase and post tests immediately after the completion of the practice phase. The retention test was administered after a 7-day retention interval. The results of repeated measures analysis of variance indicated significant improvement for the experimental groups for the serve but no significant effects of practice condition on acquisition or retention. These findings suggest that skill practice was able to produce learning effects only for the serve but do not document any benefits of serial practice schedules for learning volleyball skills during physical education classes.